Comparative Analysis of Mlipahan Signaling Intersection Performance Using Vissim Ptv Software and Mkji Method 1997 - Frenky Pratama Sejati; Sumina Sumina; Erni Mulyandari (Jurnal Syntax Admiration, 2024)
The growth of motor vehicles in Surakarta from year to year always increases while road capacity does not develop. Therefore, there are often traffic jams everywhere. The discipline of every road user also plays an important role in overcoming congestion on the highway. Stages carried out from problem formulation, research objectives, and literature review, Then preliminary surveys, geometric surveys, vehicle volume surveys, and vehicle speed surveysMonday saturation degrees (DS) decreased after changing the cycle time. This means that the traffic volume at the Mlipahan intersection has decreased due to the resetting of traffic lights on Monday Road capacity: north 1,647 smp / hour, south 1,610 smp / hour, west 786 smp / hour, east 1,348 smp / hour. Saturation Degrees: North 1.15, South 1.12, West 1.15, and East 1.13. Queue Length: North 203 m, South 195 m, West 93 m, and East 145 m. obtained a value of 210 sec/smp. Sunday obtained Road capacity: North 1,763 smp / hour, South 1,549 smp / hour, West 818 smp / hour, and East 1,050 smp / hour. Saturation Degree: North 0.54, South 0.51, West 0.95, and East 0.91. Queue Length: North 92 m, South 89 m, West 87 m, and East 104 m. And the delay was obtained at 36 sec/smp. With PTV-VISSIM software, the queue length is obtained: North 97 m, South 129 m, West 198 m, and East 83 m. The delay was obtained at 72 sec/skr. And Service Level Intersection F or poor.